Career development or career delay? Postdoctoral fellowships and the de-professionalizing of academic work in South African universities. Issue 4 (16th June 2022) - Kerr, Philippa
Abstract: This paper argues that the South African postdoctoral fellow system is de-professionalising academic work by constituting postdocs as students who receive training from the university rather than employees who work for it. Ironically, it obscures this de-professionalisation with a discourse of postdoctoral fellowships as 'professional development' opportunities. This case is made through a critical discourse analysis which contrasts the way universities construct postdoctoral fellowships on their websites with a structural analysis of the functions postdoctoral fellows fulfil within a commodifying higher education system. Postdocs produce research outputs for universities more cheaply than employees, and in a way which makes universities score better on various metrics that only count permanently-employed academics. Considering Fairclough's ideas about the relationship between semiotic and other elements of institutions, the discourse of 'professional development' serves as a delaying and distracting tactic which keeps us from asking whether academic scholars should be supported by stable employment.